Behavioral differentiation in oviposition activity in Drosophila buzzatii from highland and lowland populations in Argentina: plasticity or thermal adaptation? - Dahlgaard, J.; Hasson, E.; Loeschcke, V. (Evolution, 2001)
Highland populations of several Drosophila species in Argentina were active early in the afternoon in the field as opposed to populations from a much warmer lowland site, where flies were mainly active in the early evening prior to sunset. For one of these species, Drosophila buzzatii, we tested for a genetic component of activity differences by carrying out crosses within and between populations and measuring oviposition activity of the progeny in the laboratory. We found that activity in the highland population exceeded that in the lowland one during the midafternoon, whereas activity in the lowland population exceeded that in the highland one prior to the beginning of the dark period. Oviposition activity for the period corresponding to the field observations was regressed on the proportion of the genome derived from the highland population. This variable significantly predicted oviposition activity between 1400 and 1600 and between 2000 and 2200 h. Activity of both reciprocal crosses was intermediate and not significantly different from each other, suggesting that nuclear genetic, rather than cytoplasmic factors contribute to differences in oviposition activity between the populations. Two morphological, one genetic, and one stress resistance trait were also scored to examine whether temperature differences between environments were associated with other differences between populations. Wing length of wild-caught and laboratory-reared flies from the highland population significantly exceeded that in the lowland. Thorax length of laboratory-reared flies from the highland population also significantly exceeded that from the lowland. Chromosomal inversion frequencies differed significantly between the two populations with a fivefold reduction in the frequency of arrangement 2st in the highland as compared to the lowland population. This arrangement is known for its negative dose effect on size, and thus, the highland population has experienced a genetic change, perhaps as a result of adaptation to the colder environment, where body size and the frequency of arrangement 2st have changed in concert. Finally, a heat knockdown test revealed that the lowland population was significantly more resistant to high temperature than the highland one. In conclusion, we suggest that temperature has been an important selective agent causing adaptive differentiation between these two populations. We also suggest that the activity rhythms of the two populations have diverged as a consequence of behavioral evolution, that is, through avoidance of stressful temperatures as a mean of thermal adaptation.